Political Discourse & US Strategic Narrative in Zeb-un-Nissa Hamidullah’s Sixty Days in America - Shafaat Yar Khan; Amra Raza (Journal of Political Studies, 2017)
This research paper is a narratological analysis of the strategic construction of the worldview involving America in Zeb-un-Nissa Hamidullah’s travelogue, Sixty Days in America (1956).It studies the political discourse in the historical contextualisation of political implications of her travelogue which allowed Hamidullah to create a world view. It subjects Hamidullah’s travelogue to a narratological political discourse analysis which I a new method of analysis. It triangulates its methods of political discourse analysis with the strategies developed in contextualist-rhetorical studies. The narratological analysis, thus, focuses on the political orientation of her personal narrative and her construction of narrative situations which employ political discourse strategies to embed her ideology. The study finds narratological evidence to prove that Hamidullah presented America as a hegemonic world leader that has replaced UK. The paper identifies several narrative techniques which can be used to analyse narratives of the hegemonised third world people living under imperialist pressures.